Beneficial Effect of Human Induced Pluripotent Stem Cell-Derived Neural Precursors in Spinal Cord Injury Repair. Issue 9 (September 2015) - Romanyuk, Nataliya; Amemori, Takashi; Turnovcova, Karolina; Prochazka, Pavel; Onteniente, Brigitte; Sykova, Eva; Jendelova, Pavla
Despite advances in our understanding and research of induced pluripotent stem cells (iPSCs), their use in clinical practice is still limited due to lack of preclinical experiments. Neural precursors (NPs) derived from a clone of human iPSCs (IMR90) were used to treat a rat spinal cord lesion 1 week after induction. Functional recovery was evaluated using the BBB, beam walking, rotarod, and plantar tests. Lesion morphology, endogenous axonal sprouting, graft survival, and iPSC-NP differentiation were analyzed immunohistochemically. Quantitative polymerase chain reaction (qPCR) was used to evaluate the effect of transplanted iPSC-NPs on endogenous regenerative processes and also to monitor their behavior after transplantation. Human iPSC-NPs robustly survived in the lesion, migrated, and partially filled the lesion cavity during the entire period of observation. Transplanted animals displayed significant motor improvement already from the second week after the transplantation of iPSC-NPs. qPCR revealed the increased expression of human neurotrophins 8 weeks after transplantation. Simultaneously, the white and gray matter were spared in the host tissue. The grafted cells were immunohistochemically positive for doublecortin, MAP2, bIII-tubulin, GFAP, and CNPase 8 weeks after transplantation. Human iPSC-NPs further matured, and 17 weeks after transplantation differentiated toward interneurons, dopaminergic neurons, serotoninergic neurons, and ChAT-positive motoneurons. Human iPSC-NPs possess neurotrophic properties that are associated with significant early functional improvement and the sparing of spinal cord tissue. Their ability to differentiate into tissue-specific neurons leads to the long-term restoration of the lesioned tissue, making the cells a promising candidate for future cell-based therapy of SCI.